Lipases produzidas por fungos derivados de ambiente marinho: otimização, purificação e caracterização bioquímica - Videira, Alexandre [UNESP] (2014)
Lipases are hydrolases (triacylglycerol acylhydrolases EC 3.1.1.3) capable of hydrolyzing carboxyl esters of long-chain acylglycerol release mono- or diacyglycerol, free glycerol and fatty acid. In addition, the lipases are effective for synthesis reactions such as esterification, glycerolysis, transesterification and aminolysis, this capability related to the displacement of the equilibrium of the reaction towards synthesis or hydrolysis inherent in the concentration of water present in the medium, the characteristic that makes biocatalysts very versatile, with important biotechnological applications. Such as food, detergents, pharmaceutical, textile, leather, paper and cosmetics industries. This work aimed to identify six species of fungi that produce lipase, optimize the production of this enzyme by lineage selected and purify and characterize partially the lipase produced in optimal condition. Enzyme activity was determined after submerged cultures, aiming to increase enzyme production. The factors measured in this optimization process of lipase production were: mineral components, time of cultivation, source of carbon and nitrogen and their concentration, pH and inoculum. The use of molecular markers allowed us to identify the six lipolytic fungi until species, except for strain Fusarium sp. CBMAI 1227. The methodology of screening of fungi for the production of lipase in neutral medium allowed the selection of the isolated Trichodemra harzianum CBMAI 1229 as best producer. The evaluation of improved cultivation conditions was assayed by lipase activity, determined through hydrolysis releasing íon ρ-nitrofenol (pNP) of ρ-nitrophenyl-palmitate (pNPP) as substrate synthetic at 37 °C. The best condition for lipase production (231,58 ± 35,59 U mL-1) was reached after 120 hours of cultivation, 25 °C and 150 rpm in medium mineral Olson & Johnson (1948), suplemented with sunflower oil 3,0% (v/v), peptone 2,0% (w/v), yeast extract 0,2%...